The Impact of Stock Overvaluation on Stock’s Abnormal Returns and their Volatility over Time - Ali Ghasemi; Mohammad Reza Nikbakht (مطالعات تجربی حسابداری مالی, 2015)
This study examines the impact of stock overvaluation on abnormal stock returns and their volatility over time in listed companies of Tehran Stock Exchange. To measure stock overvaluation, Rhodes-Kropf et al (2005) research and to measure abnormal stock returns and their volatility over time, the Fama and French (1995) three-factor model has been used. The population of this study, included of 64 companies in listed companies of Tehran Stock Exchange was selected systematically, and ten-year period from 2005 to 2014 was used for the statistical & necessary tested on them. The results using multivariate linear regression using panel data and fixed effects approach suggest that stock overvaluation has a positive and significant impact on abnormal stock returns and volatility of in over time. In other words, by increasing the stock over valuation over time, abnormal stock returns and their volatility significantly increased. It is recommended to business executives by providing the necessary background for a realistic evaluation of the stock, the necessary fields in order to reduce the abnormal returns of stocks and their volatility to bring over time.